2019
DOI: 10.1155/2019/2484678
|View full text |Cite
|
Sign up to set email alerts
|

Redox Status and Muscle Pathology in Rheumatoid Arthritis: Insights from Various Rat Hindlimb Muscles

Abstract: Due to atrophy, muscle weakness is a common occurrence in rheumatoid arthritis (RA). The majority of human studies are conducted on the vastus lateralis muscle—a muscle with mixed fiber type—but little comparative data between multiple muscles in either rodent or human models are available. The current study therefore assessed both muscle ultrastructure and selected redox indicators across various muscles in a model of collagen-induced rheumatoid arthritis in female Sprague-Dawley rats. Only three muscles, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…In contrast, no difference in muscle weight and force production deficits between soleus and EDL muscles were reported in mice, suggesting that changes in gastrocnemius and EDL muscles might differ [37]. However, a recent study done by our group assessing the gastrocnemius, soleus and EDL muscles in rats, demonstrated a severe (≈60%) loss of muscle mass, but with similar severity in terms of reduction in CSA, left shift of fibre size distribution and histological evidence of fibre degradation [38], supporting the argument against muscle fibre type as major role player. Interestingly, atrophy was less pronounced in the vastus lateralis muscle, which suggests that other factors, such as body posture, distance of muscle from affected joints, or even muscle-specific differences in redox profile-which was detailed in this study [34]-may contribute relatively more to final outcome than fibre type itself.…”
Section: The Role Of Skeletal Muscle Fibre Type Compositionmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, no difference in muscle weight and force production deficits between soleus and EDL muscles were reported in mice, suggesting that changes in gastrocnemius and EDL muscles might differ [37]. However, a recent study done by our group assessing the gastrocnemius, soleus and EDL muscles in rats, demonstrated a severe (≈60%) loss of muscle mass, but with similar severity in terms of reduction in CSA, left shift of fibre size distribution and histological evidence of fibre degradation [38], supporting the argument against muscle fibre type as major role player. Interestingly, atrophy was less pronounced in the vastus lateralis muscle, which suggests that other factors, such as body posture, distance of muscle from affected joints, or even muscle-specific differences in redox profile-which was detailed in this study [34]-may contribute relatively more to final outcome than fibre type itself.…”
Section: The Role Of Skeletal Muscle Fibre Type Compositionmentioning
confidence: 72%
“…3 Representative images suggesting the presence of different cell types in healthy versus rheumatoid arthritis skeletal muscle. Fluorescent images from a RA rodent model (study execution described in Oyenihi et al, 2019 [38]; staining method described in Additional file 1) indicate clear cachexia and increased fibrosis between muscle fibres. Black and white images indicative of the authors prediction of greater presence of macrophages (M1 and M2b) and fibroblasts in RA…”
Section: A More In-depth Review Of Dysregulated Macrophage Polarizatimentioning
confidence: 99%
See 1 more Smart Citation
“…background area was subtracted from connective tissue and total tissue, then followed the formula: percentage of brosis = connective tissue/ connective tissue + total tissue x100 [25].…”
Section: Histopathological Analysis Of Muscle Tissuementioning
confidence: 99%
“…To clarify the therapeutic effect of edaravone on arthritis, a total of 45 male rats were used and divided into three groups: normal control (NC), CIA model and treatment groups. The therapy CIA groups received one of three intraperitoneal injection doses (3,6, and 9 mL/kg, twice per day) of edaravone for 2, 4, and 6 weeks, respectively.…”
Section: Introductionmentioning
confidence: 99%